Students' Perceptions of Teacher-Centered Grammar Instruction in Learning the Simple Past Tense: A Study of Grade IX Students at a Junior High School - Maulidya Azfa Shofy Fadhillah; Yousef Bani Ahmad (Journal of English Language and Education, 2026)
This study explored Grade IX students’ perceptions of teacher-centered grammar instruction in learning the Simple Past Tense at a junior high school in Karawang, West Java, Indonesia. The study was conducted because previous research has more frequently examined grammar instruction and students’ perceptions in general EFL contexts, while limited attention has been given to junior high school students’ perceptions of teacher-centered instruction for learning a specific grammatical topic. Using a qualitative descriptive design, the study examined students’ experiences of the instructional approach used during grammar lessons. Data were collected through classroom observations and semi-structured online-chat interviews with four purposively selected students. The data were analyzed using Braun and Clarke’s (2006) thematic analysis framework. Three themes emerged: instructional clarity, student engagement, and preference for interactive learning. The participants perceived teacher-centered instruction as helpful when explanations were clear and understandable; however, extended teacher-led explanations were associated with boredom and reduced attention. The students also preferred games, group work, and practical activities to complement teacher explanations. The findings indicate that teacher-centered grammar instruction can support grammatical understanding when combined with interactive activities that sustain student participation and engagement.